Studi Analisis El Nino Dan La Nina Terhadap Curah Hujan Mengunakan Fast Fourier Transform (FFT) Dan Lomb Periodogram (Studi Kasus : Provinsi Jawa Tengah - Fathony, Awal Rifan; Zakaria, Ahmad; Wijaya, Riki Chandra; Kusumaastuti, Dyah Indriana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Central Java Province is a potential area that has an important role in national food production. El Nino and La Nina events have a very large impact if they occur in Indonesia, especially in Central Java Province. This study aims to analyze the impact of El Nino and La Nina events specifically in Central Java Province where the areas more dominantly affected by El Nino and La Nina. The research location uses 3 rainfall stations, namely the Tunggal Wulung Meteorological Station, Tegal Maritime Meteorological Station, and Tanjung Emas Maritime Meteorological Station. The method used is the Fast Fourier Transform (FFT) method and the long periodogram. The results showed that the periods of El Nino and La Nina phenomena recurring using the FFT method are forecasts for the periods 2.2428, 2.8036, and 3.7381 years. While using the lom periodogram method, namely in the periods of 2,480, 2,621, and 3:16 years. The results of the analysis of the FFT method obtained results that varied in the height of rainfall at the 3 stations, while the results of the analysis using the periodogram log showed that the Tunggal Wulung rain station had the highest peak rainfall. This study concludes that there are variations in the peak incidence using either the slow periodogram or the FFT method. However, both of these methods and based on the BMKG and TRMM, the Tunggal Wulung Meteorological Station has the highest peak between Tegal Station and Tanjung Emas Station.